Analisa Prilaku Konsumen Dalam Pengambilan Keputusan Pembelian Jajanan Pasar Pada Masa Pandemi Covid-19 Di Kecamatan Delta Pawan Kabupaten Ketapang - Irianto rian; Dian Fitriani; Emi Arahman (Politeknik Negeri Lampung, 2021)
The world is currently experiencing a crisis caused by the Corona pandemic. The virus which has another name COVID-19 has also succeeded in changing people's behavior. Such as social distancing, for example, which affects changes in consumer behavior. Jajanan pasar are traditional Indonesian foods that are traded in markets, especially in traditional markets, usually made with unique tastes and attractive shapes. The purpose of this study is to determine the influence of consumer behavior factors (occupation, income, number of dependents, education level and age) in making decisions to purchase market snacks during the Covid 19 pandemic.The analytical method used is logistic regression analysis, which is one of the mathematical model approaches used to analyze the relationship of one or more independent variables with a dichotomous / binary categorical dependent variable. The results of the study explained that during the Covid pandemic 19 factors - consumer behavior factors in making decisions on buying market snacks in Delta Pawan District, Ketapang Regency, namely work, income, number of dependents, level of education and age did not have a significant effect on consumer behavior in making snack buying decisions. market in Delta Pawan District. Keywords: Covid 19, jajanan pasar, logistic regression